Accounting for intangible assets: suggested solutions. Issue 6 (19th September 2022) - Barker, Richard; Lennard, Andrew; Penman, Stephen; Teixeira, Alan
Abstract : Current accounting practice expenses many investments in intangible assets to the income statement, confusing earnings from current revenues with investments to gain future revenues. This has led to increasing calls to book those investments to the balance sheet. Drawing on relevant research, we evaluate solutions for intangible asset accounting that contrast with balance sheet recognition, and we compare these with current practice under IFRS. Key is acknowledging that an accounting solution comes from a double-entry system, which produces both an income statement and a balance sheet, and which has features that both enable and limit the information that can be conveyed about intangible asset value. In this system, asset recognition in the balance sheet must consider the effect on measurement in the income statement, for the income statement conveys value added to investment on the balance sheet. A determining feature is uncertainty about investment outcome and how that affects the income statement, so our solutions centre on accounting under uncertainty. Two other accounting features are added: there has to be an investment expenditure for balance sheet recognition, and that expenditure must be separately identifiable from transactions. These features, rather than the tangible-intangible asset dichotomy, lead to the prescribed solutions.